Prostate-specific antigen testing rates remain low in UK general practice: a cross-sectional study in six English cities. - Williams, N; Hughes, L; Turner, E; Donovan, J; Hamdy, F; Neal, D; Martin, R; Metcalfe, C (2011)
OBJECTIVE • To estimate rates of prostate-specific antigen (PSA) testing in UK general practices by age, deprivation index and geographical location. SUBJECTS AND METHODS • Practice-based, retrospective data on PSA testing patterns in 2007 were collected from a random sample of 87 general practices using EMIS LV computer systems within the passively observed non-intervention arm of a cluster-randomized controlled trial. • Information for a total of 126 716 men aged 45-89 years with no recorded diagnosis of prostate cancer prior to 1 January 2007 was collected. RESULTS • In all, 7902 (6.2%) of 126 716 men aged 45-89 without a prior diagnosis of prostate cancer underwent at least one PSA test from their general practitioner during 2007 [95% confidence interval (CI) 5.6-7.0%; practice-based inter-quartile range 3.6-8.4%]. • PSA testing rates were 1.4% (95% CI 1.1-1.6%) in men aged 45-49, rising to 11.3% (95% CI 10.0-12.9%) at age 75-79 years (P for trend <0.001). • Testing rates were lowest in the three northern centres (3.5-5.7%) vs the three more southern centres (7.1-8.9%; P < 0.001). • For every 20 points increase in the index of multiple deprivation score, the proportion of men tested fell by 1.7% (95% CI -2.5 to -0.8%; P < 0.001). • Lower proportions of men were subsequently diagnosed with prostate cancer in practices testing more men (odds ratio for a one unit increase in the natural log of testing 0.76; 95% CI 0.60-0.97; P= 0.025). CONCLUSION • Overall levels of PSA testing in UK general practice remain low, but for those tested there are important variations by age, deprivation and geographical location that do not appear to reflect clinical need or the intention of current policy. • PSA testing in general practice is currently skewed towards older men, and current policy enabling all men to make an informed choice about PSA testing is not being effectively implemented as uptake clearly varies by socioeconomic status. • This reinforces the need for robust evidence regarding the costs and benefits of using the PSA test for the detection of localized prostate cancer in the UK, a full assessment of the health economic implications and a revision of the current policy.